Pengaruh Promosi Terhadap Keputusan Pembelian - Maria Agatha Sri Wdyanti Hastuti; Muhammad Anasrulloh (Fakultas Ekonomi Universitas Panca Marga, 2020)
A place to live is an important requirement for students because where they live they can rest after carrying out the process of learning activities during campus or after doing other activities. For that they need a place to live, whether they choose to live with their family for those who have a family in the city where the college is located or a boarding house that suits their needs. A boarding house is a type of rental room that is rented (booked) for a certain period of time. Generally, a room rental is carried out for a period of one year and has a function as a temporary residence. The function of this boarding house is what makes migrant students prefer alternative boarding houses because of the cost and time saving considerations because a nearby place will be the initial destination for someone to move. The boarding house has a positive function, namely a place as a temporary house, a place to study, and a place to rest. If it is related to the function of boarding houses, it is found that there are many phenomena of moving boarding houses carried out by tenants. In order to get a boarding house as desired, there are several factors that students may consider before deciding which boarding house to choose. This study aims to determine the effect of promotion on student decisions in choosing boarding houses in Tulungagung.